Analisis Kualitas Pelayanan Jasa Perbankan Syariah Dengan Metode Fuzzy-Service Quality Studi Pada Bank Syariah Indonesia Kantor Cabang Pembantu Kisaran - Fahmiatul Aulia Pangaribuan; Ahmad Amin Dalimunthe; Muhammad Ikhsan Harahap (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2023)
This study aims to see and analyze how the service quality at Bank Syariah Indonesia KCP Kisaran uses the Fuzzy-Service Quality method. The method used in this study is a qualitative approach. The sampling technique is random sampling. The sample used was 100 people with a Likert scale-based questionnaire for data collection. Based on the results of defuzzification calculations, the highest perceived value of service quality for BSI Sub-Branch Offices is 76,5. For defuzzification calculations, it is known that the highest expectation value of BSI service quality is 91,25. Meanwhile, the gap between perceptions and expectations shows a negative value, namely -1,64 or not 1, meaning that what the customer expects is not fully in accordance with what is received by Bank Syariah Indonesia customers at the Kisaran Sub-Branch Office.